ANALISIS ORGANIZATIONAL CITIZENSHIP BEHAVIOR, BUDAYA ORGANISASI, KOMUNIKASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA SDM (GURU) GROWING HOPE - Pertiwi, Ratih; Sanusi, Anuar; Fauzi, Fauzi (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2023)
This research aims to conduct a study on improving teacher performance through Organizational Citizenship Behavior, Communication Organizational Culture and Leadership Style at PKLK Growing Hope Bandar Lampung, Lampung. The study was conducted on 4 variables, namely Organizational Citizenship Behavior, Communication Organizational Culture and Leadership Style to improve teacher performance at PKLK Growing Hope Bandar Lampung, Lampung. Model analysis uses Structural Equation Modeling. The analysis tool used is Partial Least Square (PLS) with Smart PLS 3.0 software starting from measuring the model (outer model), model structure (inner model), and hypothesis testing. The research results show that there is a significant influence of Organizational Citizenship Behavior on Teacher Performance, proving that there is a significant influence of Organizational Culture on Teacher Performance, there is a significant influence of Communication on Teacher Performance. Simultaneously testing the hypothesis also shows that there is a significant influence of Leadership Style on Teacher Performance. Positive and significant correlation between the variables Organizational Citizenship Behavior, Communication Organizational Culture and Leadership Style with increasing teacher performance at PKLK Growing Hope Bandar Lampung, Lampung. The R Square measurement results have a value of 95% while 5% is outside the variables studied. This shows that there are several other variables that can be studied to improve this research.